Efficient Water Oxidation Catalyzed by Mononuclear Ruthenium(II) Complexes Incorporating Schiff Base Ligands. Issue 26 (2nd June 2014) - Li, Ting‐Ting; Chen, Yong; Li, Fu‐Min; Zhao, Wei‐Liang; Wang, Chuan‐Jun; Lv, Xiao‐Jun; Xu, Quan‐Qing; Fu, Wen‐Fu
Abstract Four new charge‐neutral ruthenium(II) complexes containing dianionic Schiff base and isoquinoline or 4‐picoline ligands were synthesized and characterized by NMR and ESI‐MS spectroscopies, elemental analysis, and X‐ray diffraction. The complexes exhibited excellent chemical water oxidation activity and high stability under acidic conditions (pH 1.0) using (NH4)2Ce(NO3)6 as a sacrificial electron acceptor. The high catalytic activities of these complexes for water oxidation were sustained for more than 10 h at low concentrations. High turnover numbers of up to 3200 were achieved. A water nucleophilic attack mechanism was proposed. A RuVO intermediate was detected during the catalytic cycle by high‐resolution mass spectrometry.